Without ever reaching the summit : a journey - Cognetti, Paolo, 1978- (HarperOne, 2020)
"In this exquisitely written journal-turned-journey of self-discovery, international bestselling author Paolo Cognetti examines our universal desire for connection through a voyage in the Himalayas. Why climb a mountain without ever reaching the summit? In 2017, Paolo Cognetti returned to Nepal, not to conquer the mountains but to journey through the high valleys of the Dolpo with a copy of Peter Matthiessen's The Snow Leopard in hand. Drawing on memories of his childhood in theAlps, Cognetti explored the roots of life in the mountains, truly getting to know the communities and the nature that forged this resilient, almost mythical region. Accompanying him was Remigio, a childhood friend who had never left the mountains of Italy, and Nicola, a painter he had recently met. Joined by a stalwart team of local sherpas, the trio started out in the remote Dolpo region of Nepal. From there, a journey of self-discovery shaped by illness, human connection, and empathy was born. Without Ever Reaching the Summit features line illustrations drawn by the author"--